Strategi Pemasaran Menggunakan Matriks SWOT dan QSPM pada Pupuk Non-Subsidi NPK Pelangi PT Pupuk Kaltim - Purwadi, Rendi; Suharno, Suharno; Zainurossalamia ZA, Saida (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
Fertilizer is a supporter of food security, the existence of AFTA provides opportunities for Indonesian fertilizer producers to open up global markets as well as being a challenge for the domestic fertilizer industry. Determining where the position of non-subsidized NPK Pelangi fertilizer in facing market competition and implementing the best strategy to increase sales of non-subsidized NPK Pelangi fertilizer is very necessary for the company. The stages carried out in the research are as follows, the data collection stage through interviews and questionnaires and the IFE and EFE Matrix data processing stages, the analysis stage using the SWOT Matrix and the decision-making stage using the QSPM Matrix. Based on the analysis of the internal and external matrix (IE), the non-subsidized NPK Pelangi fertilizer is located in quadrant IV, namely Grow and Build and the best strategy that can be carried out internally is the Market Development Strategy with the highest score of TAS 6,226, namely marketing non-subsidized NPK fertilizer products. Pelangi collaborates with the Prosperous Program Makmur.